Design and simulation of electrically pumped mode-locked VECSELs - Witzigmann, Bernd; Dahhan, Imad; Kreuter, Philipp; Barbarin, Yohan; Hofmann, Martin; Pallmann, Wolfgang; Golling, Mattthias; Suedmeyer, Thomas; Keller, Ursula (Proceedings of SPIE - The International Society for Optical Engineering, 2011)
Vertical External Cavity Surface Emitting Lasers (VECSELs) feature scaling to large active areas and combine surface emission with high optical power output. In principle, they can be designed with electrical pumping operating in continuous wave or passively mode-locked operation. In this paper, our design and modeling activities towards a high power passively mode-locked VECSEL are described. In particular, design towards single mode high-power CW operation is discussed as prerequisite for passive mode-locking.
CRIS-Team Scopus Importer:2021-06-11
Keywords: External cavity laser; Semiconductor laser; Simulation